HUBUNGAN PERSONAL HIGIENE DENGAN KEJADIAN PEDICULOSIS CAPITIS PADA SANTRIWATI DI PONDOK PESANTREN ROHMATUL QUR’AN MEJOBO KUDUS - Erna Setiyani; Tri Mulyowati; Rinda Binugraheni (Jurnal Labora Medika, 2021)
Pediculosis is an infectious disease caused by the parasite Pediculus humanus capitis. In Yogyakarta, the prevalence of pediculosis incidence is 19.6%. The priority for handling cases of Pediculosis capitis is very low and is considered not life-threatening. Pediculosis capitis is often related to personal hygiene. The purpose of this study was to determine the relationship between personal hygiene and the incidence of Pediculosis capitis at the Rohmatul Qur'an Islamic Boarding School Mejobo Kudus. The examination used a direct method with descriptive research type to describe the relationship of personal hygiene with the incidence of Pediculosis. This study uses a cross-sectional approach, namely data collection to measure the independent and dependent variables at the same time. The sample used is the entire population of 63 respondents. The results of the examination of 63 female students, 44 (69.8%) female students at the Rohmatul Qur'an Islamic Boarding School were positive for Pediculosis capitis. The personal hygiene of the female students at the Rohmatul Qur'an Islamic Boarding School in Mejobo Kudus was mostly not good as many as 39 (61.9%) personal hygiene was good 24 (38.1%). The conclusion of this study is that there is a relationship between personal hygiene and the incidence of Pediculosis capitis at the Rohmatul Qur'an Islamic Boarding School Mejobo Kudus with a P-value of 0.033 (α; 0.05).